Психопоэтологическая парадигма мысль – слово в повестях Ивана Андрусяка для / про подростков - Kuca, Larisa (Slavia Centralis, 2020)
The article suggests the interpretation of two stories by modern Ukrainian writer Ivan Andrusiak from the point of view of psychopoetics as a way of expressing thought through linguistic means. The changes in the poetological system of modern teenage literature in the direction towards modern significant works and the author’s appeal to deep reflection levels have been illustrated. In the context of interdisciplinary discourse, special attention has been paid to the phenomenon of silence as a communicative invariant. The article explains Ivan Andrusiak’s appeal to irrational dimensions of thought and the actualisation of linguistic creation of dream spaces, appropriate for the teens’ age, viewed as a means of accentuating teenagers’ crisis states. The multifunctional character of displaying the beautiful in the analysed stories has been viewed. The poetics of creating the spiritual odyssey of an unusual modern child within interdisciplinary connections has been generalised.
Keywords: teenage literature; psychopoetics; text stereometry; time and space; sacral time and space; dream space; silence; ideal